2009
DOI: 10.1161/strokeaha.109.554824
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Brain Matrix Metalloproteinase-9 After Acute Focal Cerebral Ischemia in Rats

Abstract: Background and Purpose Plasma levels of matrix metalloproteinase-9 (MMP-9) have been proposed to be a useful biomarker for assessing pathological events in brain. Here, we examined the temporal profiles of MMP-9 in blood and brain using a rat model of acute focal cerebral ischemia. Methods Plasma and brain levels of MMP-2 and MMP-9 were quantified at 3, 6, 12, and 24 hours after permanent middle cerebral artery occlusion in male Sprague-Dawley rats. Infarct volumes at 24 hours were confirmed with 2,3,5-triph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 32 publications
6
83
1
Order By: Relevance
“…3). In consistent with the previous report (Park et al 2009), the proMMP9 level was increased 24 h after HI injury as compared to the sham level (data not shown). Future study is required to investigate the pro-MMPs and their transcriptional levels after HI injury.…”
Section: Discussionsupporting
confidence: 93%
“…3). In consistent with the previous report (Park et al 2009), the proMMP9 level was increased 24 h after HI injury as compared to the sham level (data not shown). Future study is required to investigate the pro-MMPs and their transcriptional levels after HI injury.…”
Section: Discussionsupporting
confidence: 93%
“…31 For in vivo studies, using the same ischemic mouse models, we previously observed during the course of experiments that MMP-9 levels were dramatically unregulated and activated while MMP-2 levels remained similar in the ischemic cortex and the non-lesioned cortex, suggesting that MMP-9 is the predominant gelatinase involved, at least under our experimental conditions. 8,20,21,32 Our observations are consistent with the studies of Lo and others, [33][34][35] suggesting that there is only low level induction of MMP-2 after cerebral ischemia in rodent models; moreover, these levels of MMP-2 are much lower than those of MMP-9. Similar results were found in brain tissues and blood from human stroke patients showing increased MMP-9 levels.…”
Section: Discussionsupporting
confidence: 91%
“…MMPs also play a crucial role in brain inflammation by increasing blood-brain barrier permeability through the destruction of extracellular matrix (Park et al, 2009). Neutrophil infiltration contributes to the increase in MMP-9 in the ischemic brain (Justicia et al, 2003) of stroke patients (Lo et al, 2003).…”
Section: /Ach3mentioning
confidence: 99%